The correlation of urinary podocytes and podocalyxin with histological features of lupus nephritis. (March 2018) - Ikuma, D; Hiromura, K; Kajiyama, H; Suwa, J; Ikeuchi, H; Sakairi, T; Kaneko, Y; Maeshima, A; Kurosawa, H; Hirayama, Y; Yokota, K; Araki, Y; et al.
Objectives: The objective of this study was to test the correlation of urinary podocyte number (U-Pod) and urinary podocalyxin levels (U-PCX) with histology of lupus nephritis. Methods: This was an observational, cross-sectional study. Sixty-four patients were enrolled: 40 with lupus nephritis and 24 without lupus nephritis (12 lupus nephritis patients in complete remission and 12 systemic lupus erythematosus patients without lupus nephritis). Urine samples were collected before initiating treatment. U-Pod was determined by counting podocalyxin-positive cells, and U-PCX was measured by sandwich ELISA, normalized to urinary creatinine levels (U-Pod/Cr, U-PCX/Cr). Results: Lupus nephritis patients showed significantly higher U-Pod/Cr and U-PCX/Cr compared with patients without lupus nephritis. U-Pod/Cr was high in proliferative lupus nephritis (class III±V/IV±V), especially in pure class IV (4.57 (2.02–16.75)), but low in pure class V (0.30 (0.00–0.71)). U-Pod/Cr showed a positive correlation with activity index ( r =0.50, P =0.0012) and was independently associated with cellular crescent formation. In contrast, U-PCX/Cr was high in both proliferative and membranous lupus nephritis. Receiver operating characteristic analysis revealed significant correlation of U-Pod/Cr with pure class IV, class IV±V and cellular crescent formation, and the combined values of U-Pod/Cr and U-PCX/Cr were shown to be associated with pure class V. Conclusions: U-Pod/Cr and U-PCX/Cr correlate with histological features of lupus nephritis.